Pengaruh Work-Family Conflict terhadap Psychological Well-Being Perawat yang Bekerja di RSUP Dr. M. Djamil Padang Melalui Work-Life Balance - Annesya Effendy; Rini Sarianti (Pusat Riset dan Inovasi Nasional, 2025)
Dr. M. Djamil Central General Hospital Padang is a type-A teaching hospital and the main referral center in Central Sumatra, where nurses especially married women face high work demands and rotating shifts, creating challenges in balancing professional and family roles. This study aims to examine the effect of work-family conflict on the psychological well-being of female nurses, with work-life balance as a mediating variable. The core issue addressed is the imbalance between occupational responsibilities and family obligations that may negatively impact psychological well-being. A quantitative approach was used, with a survey conducted on 104 married female nurses with children. Data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM–PLS) method via the SmartPLS 4 application. The results show that work-family conflict negatively affects both psychological well-being and work-life balance, while work-life balance positively and significantly affects psychological well-being. Additionally, work-life balance significantly mediates the relationship between work-family conflict and psychological well-being. These findings emphasize the importance of balancing work and personal life to maintain nurses’ mental health. Therefore, organizational support such as flexible work policies and psychological wellness programs is essential to improve both professional performance and personal well-being among nurses.